Soluble epoxide hydrolase inhibition improves cognitive function and parenchymal artery dilation in a hypertensive model of chronic cerebral hypoperfusion. (4th September 2020) - Matin, Nusrat; Fisher, Courtney; Lansdell, Theresa A.; Hammock, Bruce D.; Yang, Jun; Jackson, William F.; Dorrance, Anne M.
Abstract: Objective: Parenchymal arterioles (PAs) regulate perfusion of the cerebral microcirculation, and impaired PA endothelium‐dependent dilation occurs in dementia models mimicking chronic cerebral hypoperfusion (CCH). Epoxyeicosatrienoic acids (EETs) are vasodilators; their actions are potentiated by soluble epoxide hydrolase (sEH) inhibition. We hypothesized that chronic sEH inhibition with trifluoromethoxyphenyl‐3 (1‐propionylpiperidin‐4‐yl) urea (TPPU) would prevent cognitive dysfunction and improve PA dilation in a hypertensive CCH model. Methods: Bilateral carotid artery stenosis (BCAS) was used to induce CCH in twenty‐week‐old male stroke‐prone spontaneously hypertensive rats (SHSRP) that were treated with vehicle or TPPU for 8 weeks. Cognitive function was assessed by novel object recognition. PA dilation and structure were assessed by pressure myography, and mRNA expression in brain tissue was assessed by qRT‐PCR. Results: TPPU did not enhance resting cerebral perfusion, but prevented CCH‐induced memory deficits. TPPU improved PA endothelium‐dependent dilation but reduced the sensitivity of PAs to a nitric oxide donor. TPPU treatment had no effect on PA structure or biomechanical properties. TPPU treatment increased brain mRNA expression of brain derived neurotrophic factor, doublecortin, tumor necrosis factor‐alpha, sEH, and superoxide dismutase 3, Conclusions: These data suggest that sEH inhibitors may be viable treatments for cognitive impairments associated with hypertension and CCH.